Decade review of mandible fractures and arch bar impact on outcomes of nonsubcondylar fractures. (22nd September 2015) - Kopp, Robert W.; Crozier, Daniel L.; Goyal, Parul; Kellman, Robert M.; Suryadevara, Amar C.
Abstract : Objectives/Hypothesis: Review trends in mandible fracture management and outcomes in patients treated with and without intraoperative arch bar use. Study Design: Retrospective chart review. Methods: All patients with mandible fractures between October 1, 2001, and October 1, 2011, were reviewed. Excluded were those with concomitant midfacial fractures or inadequate follow‐up. Results: Overall, 734 patients sustained 1, 312 mandible fractures. Assault was the most common etiology. The parasymphyseal, subcondylar, and angle regions were most likely fractured. In total, 85% of patients underwent open‐reduction internal‐fixation (ORIF). This overall number had no significant annual deviation. However, use of arch bars to achieve intraoperative maxillomandibular fixation (MMF) with ORIF decreased annually, whereas the use of manual reduction with ORIF increased annually. These trends held statistical significance. Outcomes were reviewed in patients with one or two nonsubcondylar fractures by assessing complications of malocclusion, infection, and malunion. In 228 patients meeting criteria, the incidence of complications was 12.9% in those treated using intraoperative arch bars with ORIF and 12.5% in those using manual reduction with ORIF. When assessing individual complications, there was no statistically significant difference. Conclusion: Our data suggest a shifting trend in mandible fracture management. Our techniques for achieving fracture reduction ideal for ORIF favors manual reduction over the use of arch bars in select cases. We found no statistical increase in the incidence of complications when using manual reduction with ORIF in patients with one and two nonsubcondylar fractures. In appropriately selected cases, manual stabilization of fractured segments is an alternative to using arch bars to achieve intraoperative MMF. Level of Evidence: 4. Laryngoscope, 126:596–601, 2016